1978
DOI: 10.1073/pnas.75.3.1369
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones control lysosomal enzyme activities in liver and skeletal muscle

Abstract: Because protein degradation in liver and skeletal muscle is increased by thyroid hormones and decreased by thyroidectomy, we investigated the influence of thyroid hormones on the level of lysosomal enzymes. Hypophysectomized rats received daily injections of L-thyroxine or L-triiodothyronine. After 3 days of this regimen, homogenates of liver and skeletal muscle showed a 2-to 3-fold increase in the activities of cathepsin D, cathepsin B, and other lysosomal enzymes including leucine aminopeptidase, acid phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(58 citation statements)
references
References 25 publications
6
51
1
Order By: Relevance
“…While we do not have direct experimental evidence, several observations suggest a close relationship. Inhibition of lysosomal cathepsins may reduce intracellular protein breakdown by up to 70 % [24][25][26], whereas protein degradation has been shown to be paralleled by enhanced cathepsin activity [27][28][29][30]. These findings support the view that lysosomal proteinases are related to intracellular protein turnover, such that reduced activity would favour protein accumulation.…”
supporting
confidence: 77%
“…While we do not have direct experimental evidence, several observations suggest a close relationship. Inhibition of lysosomal cathepsins may reduce intracellular protein breakdown by up to 70 % [24][25][26], whereas protein degradation has been shown to be paralleled by enhanced cathepsin activity [27][28][29][30]. These findings support the view that lysosomal proteinases are related to intracellular protein turnover, such that reduced activity would favour protein accumulation.…”
supporting
confidence: 77%
“…In an attempt to elucidate this last aspect, Tenore et al (15) found a positive correlation between the changes of serum HEX and thyroxin levels in newborns. The potential role of thyroxin in HEX activity has been formerly suggested by the finding of approximately 50% of the normal HEX level in skeletal muscle and liver of thyroidectomized rats (19). A positive correlation between thyroxin level and serum HEX activity has been reported in euthyroid, hypothyroid and hyperthyroid prepuberal females (20), suggesting the influence of this hormone on human HEX activity as well.…”
Section: Discussionmentioning
confidence: 94%
“…The metabolic effects of hyperthyroidism have been well characterized with respect to increased oxygen consumption (1,2), augmented adipose tissue lipolysis (3,4), and net protein catabolism (5,6). The effects of hyperthyroidism on hepatic gluconeogenesis have been less clearly established.…”
Section: Introductionmentioning
confidence: 99%